PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAH, IMPLEMENTASI SISTEM INFORMASI MANAJEMEN DAERAH, DAN SISTEM PENGENDALIAN INTERNAL PEMERINTAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN SELUMA - Tri Ikyarti; Nila Aprila (Jurnal Akuntansi, 2019)
Effect of application of government accounting standards, implementation of regional management information systems, and government internal control systems on the quality of financial statements at the regional government of seluma district. This research used a quantitative approach, using primary data through questionnaires. Respondents of this research were 26 OPD of part of a financial manager a the regonal governmnt of seluma district. The Variables in thiss researcch is the government accounting standards, implementation of regional management information systems, and govrnment internal contcl systems as independent variables, as well the qualty of local governmnt financiial statements as the dependent variable. The data were analyzed with multiple regression method. The results of hypothesis shown that the government accounting standards, implementation of regional management information systems, and governent internal contral systems give the impact add it was positive to the qality of financial statemnts at the ragional govermment of seluma district.Key words: Management Information Systems, And Government internal Control Systems.